Risk management in biobanking - A. L. Borisova; M. S. Pokrovskaya; A. N. Meshkov; A. V. Kontsevaya; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2022)
Risk management is a key aspect of the organization and management of biobanks, which is part of the overall quality management system aimed at early detection, analysis and minimization of events, that can lead to negative consequences for the biobank, as well as affect the quality of biosamples and related data. The article presents the biobanking risk classification with the description of each category.Aim. To develop and implement the methodology for identification, analysis, evaluation and development of risk management measures for the biobanking process in the biobank of the National Medical Research Center for Therapy and Preventive Medicine.Material and methods. We present the methodology of the risk management process developed on the basis of the literary data, world experience and experience of the biobank of the National Medical Research Center for Therapy and Preventive Medicine.Results. The biobanking risk management procedure was developed and implemented in the biobank of the National Medical Research Center for Therapy and Preventive Medicine in 2020. The work carried out made it possible to identify, analyze and evaluate a wide range of potential negative events and actions that could lead to biobank damage, both in the form of financial losses and ethical and technical issues related to the biobanking process. A significant reduction in the frequency of emergency events and the high stability of the biobank operation under the influence of various external factors prove the effectiveness of the approach used.Conclusion. The creation and maintenance of a risk management system in the biobank allows, in combination with other measures, to ensure the safety and high quality of the procedures for collecting, processing and long-term storage of biomaterial and related data by creating an environment that rules out or minimizes the impact of various risks.